2005
DOI: 10.1002/cne.20738
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortex in the rat: Projections to subcortical autonomic, motor, and limbic centers

Abstract: This paper describes the quantitative areal and laminar distribution of identified neuron populations projecting from areas of prefrontal cortex (PFC) to subcortical autonomic, motor, and limbic sites in the rat. Injections of the retrograde pathway tracer wheat germ agglutinin conjugated with horseradish peroxidase (WGA-HRP) were made into dorsal/ventral striatum (DS/VS), basolateral amygdala (BLA), mediodorsal thalamus (MD), lateral hypothalamus (LH), mediolateral septum, dorsolateral periaqueductal gray, do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

96
966
2
18

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,065 publications
(1,110 citation statements)
references
References 130 publications
96
966
2
18
Order By: Relevance
“…In line with this, Homayoun and Moghaddam (2007) have recently shown that clozapine and haloperidol share the ability to markedly inhibit a small subset of mPFC neurons. Furthermore, only around 5% of projection neurons in the V layer of the mPFC project to the dorsal raphe nucleus, according to Gabbott et al (2005). Thus, it is conceivable that under the conditions of the present study (increased 5-HT and glutamate transmission in the mPFC) haloperidol may be able to inhibit a subpopulation of pyramidal cells (blockade of increased glutamate efflux), though sparing cortico-raphe projections.…”
Section: Discussionmentioning
confidence: 59%
“…In line with this, Homayoun and Moghaddam (2007) have recently shown that clozapine and haloperidol share the ability to markedly inhibit a small subset of mPFC neurons. Furthermore, only around 5% of projection neurons in the V layer of the mPFC project to the dorsal raphe nucleus, according to Gabbott et al (2005). Thus, it is conceivable that under the conditions of the present study (increased 5-HT and glutamate transmission in the mPFC) haloperidol may be able to inhibit a subpopulation of pyramidal cells (blockade of increased glutamate efflux), though sparing cortico-raphe projections.…”
Section: Discussionmentioning
confidence: 59%
“…The layer V pyramidal neurons in ACd integrate widespread inputs from various brain regions (Hoover and Vertes, 2007) and project to multiple subcortical areas, including striatum, amygdala, dorsal raphe, and spinal cord (Gabbott et al, 2005), to facilitate emotional expression, motor coordination, and temporal organization of behavior. In adult mice with early-life stressful experiences and vehicle treatment, mPFC-dependent cognition, including certain aspects of attention (reflected by the percentage of same arm returns) and temporal order memory, was markedly impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Brains were sectioned coronally on a freezing microtome (American Optical Corporation, Buffalo, NY) at 40 mm through the brain and stored in 0.1% NaN 3 in 1 Â phosphate-buffered saline (PBS) at 41C. The adult rat mPFC (Figure 2a), equivalent to the human dorsolateral prefrontal cortex, spans an area of 3 mm 3 bilaterally along the rostral-caudal levels of the rodent brain (Gabbott et al, 2005). Anatomically, the mPFC is clearly distinguished from other cortical areas in bregma regions 4.20-2.70 of the adult rodent brain (Kodama et al, 2004).…”
Section: Immunohistochemistrymentioning
confidence: 99%